Identitas Kimia Calon Guru Kimia: Studi Cross-Sectional pada Berbagai Angkatan Masuk - Azwa Fadilla Wafiq; Oktavia Sulistina; Anugrah Ricky Wijaya (Postgraduate, University of Mataram, 2026)
Chemistry identity shapes students’ engagement and persistence in learning chemistry. This study profiled chemistry identity among Chemistry Education students, examined differences across entry cohorts, and tested gender differences in chemistry identity. A quantitative cross-sectional survey was conducted with 176 students from the Chemistry Education Study Program at Universitas Tanjungpura using the 20-item Measure of Chemistry Identity (MoChI) on a 5-point Likert scale (overall reliability α = 0.91). Overall chemistry identity did not differ significantly across cohorts (p = .755), and no significant cohort differences were found in any MoChI subconstruct. Descriptively, value-related interest was the strongest component (M = 4.21–4.48), whereas feeling-related interest was the next strongest (M = 3.72–3.88). Mastery experiences (M = 3.29–3.49) and verbal persuasion (M = 3.09–3.23) were moderate, while internalized identity was the weakest dimension (M = 2.98–3.41). A Mann–Whitney U test showed a significant gender difference, with male students scoring higher than female students (p = .008, r ≈ .20). These findings suggest that students generally perceive chemistry as valuable, but internalizing a “chemistry person” identity remains less developed and requires more structured mastery experiences, credible recognition, and supportive learning environments for development.